2015
DOI: 10.1016/j.pragma.2014.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Pointing and reference reconsidered

Abstract: Current semantic theory on indexical expressions claims that demonstratively used indexicals such as this lack a referent-determining meaning but instead rely on an accompanying demonstration act like a pointing gesture. While this view allows to set up a sound logic of demonstratives, the direct-referential role assigned to pointing gestures has never been scrutinized thoroughly in semantics or pragmatics. We investigate the semantics and pragmatics of co-verbal pointing from a foundational perspective combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Extensive empirical work by Lücking, Pfeiffer, Rieser and colleagues at the University of Bielefeld (Kranstedt et al, 2006; Lücking et al, 2015) using highly sophisticated recording and visualization equipment has demonstrated that pointing gestures seldom if ever function as unique identifiers of a demonstratum, as proposed by Kaplan (1978). In all but the simplest situations, the identification of the demonstratum among the objects in the pointing cone identified by a pointing gesture is a complex reasoning process involving consideration of a number of additional aspects of the Interaction Situation.…”
Section: Much Of Our Grammatical Competence Concerns Language Use mentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive empirical work by Lücking, Pfeiffer, Rieser and colleagues at the University of Bielefeld (Kranstedt et al, 2006; Lücking et al, 2015) using highly sophisticated recording and visualization equipment has demonstrated that pointing gestures seldom if ever function as unique identifiers of a demonstratum, as proposed by Kaplan (1978). In all but the simplest situations, the identification of the demonstratum among the objects in the pointing cone identified by a pointing gesture is a complex reasoning process involving consideration of a number of additional aspects of the Interaction Situation.…”
Section: Much Of Our Grammatical Competence Concerns Language Use mentioning
confidence: 99%
“…The answers get introduced into the semantics via mechanisms discussed in Lücking et al (2015), whereas the question via domain specific (or alternatively genre–based ) inference (Larsson, 2002; Ginzburg, 2012) 23 .…”
Section: Grammar For Interaction : Principles and Illustrationmentioning
confidence: 99%
“…Finally, there are a number of psycholinguistic studies that have examined the multimodal use of demonstratives with experimental methods (e.g., Bangerter, 2004 ; Piwek et al, 2008 ; Lücking et al, 2015 ; Cooperrider, 2016 ; Garciá et al, 2017 ). Most of this research is concerned with demonstratives and pointing, but Garciá et al (2017) looked at the interaction between demonstratives and gaze (see also Todisco et al, 2020 and Stukenbrock, this volume).…”
Section: Introductionmentioning
confidence: 99%
“…Other things being equal, the gestural use of demonstratives is much more frequent for nearby referents than for referents far away (see also Piwek et al, 2008 ). Since far-away referents are often difficult to identify by gesture ( Lücking et al, 2015 ), one might hypothesize that the correlation between distance and pointing is ultimately motivated by the ambiguity of distant pointing. Good evidence for this hypothesis comes from a study by Cooperrider (2016) , who found that speakers extend the gestural use of demonstratives to far-away referents if they are given a laser pointer, making it possible to identify a distant referent that cannot be unambiguously identified by manual gesture.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of joint action between two agents, pointing is typically taken by adults (and children) to result in joint attention. Whether used on its own or integrated with speech, it can, however, convey a much wider range of interpretations [13][14][15][16] .…”
mentioning
confidence: 99%